1997
DOI: 10.1093/ajcn/65.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat and insulin sensitivity in a triethnic population: the role of obesity. The Insulin Resistance Atherosclerosis Study (IRAS)

Abstract: From the Insulin Resistance Atherosclerosis Study (IRAS), 1173 men and women of African-American, non-Hispanic white, and Hispanic ethnicity with no history of diabetes were included in an evaluation of the cross-sectional relation of habitual dietary fat intake with insulin sensitivity (SI) as assessed by minimal-model analysis of a 12-sample, insulin-modified frequently sampled intravenous-glucose-tolerance test. Dietary intake was measured by a food-frequency interview modified to enhance sensitivity to foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
3
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 52 publications
9
97
3
2
Order By: Relevance
“…In particular, a higher ratio of carbohydrate to fat consumption has previously been associated with improved insulin sensitivity [24,25,26]. While fasting insulin levels in this study were reduced in conjunc- tion with the HOMA beta cell function index, the HOMA insulin resistance index just failed to reach statistical significance (p=0.08).…”
Section: Dietary Interventioncontrasting
confidence: 48%
“…In particular, a higher ratio of carbohydrate to fat consumption has previously been associated with improved insulin sensitivity [24,25,26]. While fasting insulin levels in this study were reduced in conjunc- tion with the HOMA beta cell function index, the HOMA insulin resistance index just failed to reach statistical significance (p=0.08).…”
Section: Dietary Interventioncontrasting
confidence: 48%
“…14,15,45 In summary, this study shows that adverse patterns of fatty acids and DA are already associated with overweight and insulin resistance before adulthood. Results of observational and clinical studies conducted in humans have shown that a diet high in total or saturated fat is associated with abnormal glucose concentrations 3,46,47 or insulin resistance, 3,48 whereas diets enriched in monounsaturated fat 39,49 or Serum fatty acids and CVD risk factors in overweight adolescents LM Steffen et al linoleic acid 50 improve insulin sensitivity. Beneficial changes in the CE fatty acid profile and DA ratios were related to improved insulin sensitivity in a population at risk for type 2 diabetes.…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%
“…High-fat diets have been associated with a detrimental effect on glucose homeostasis in epidemiological and intervention studies (Mayer-Davis et al, 1997). There is little evidence on the role of nuts, but it seems that, despite being rich in fat, they do not negatively affect glucose homeostasis.…”
Section: Effects Of Nuts On Glucose Metabolismmentioning
confidence: 99%